Analyzing Pronunciation Problem with Fricative Consonant Among UIN Malang Students - Rohmana, Wahyu Indah Mala; Mustofa, Fikri Wasilul; Purnama, Zulfikar Ade (International Journal of English Education and Linguistics (IJoEEL), 2025)
This study examines how phonological transfer from different regional accents affects the articulation of fricative consonants /f/, /v/, /θ/, and /ð/, leading to systematic pronunciation variations. Unlike previous research that broadly investigates Indonesian-English phonological differences, this study highlights how regional accents further shape L2 pronunciation patterns. Using qualitative research, data were collected through spoken language analysis and in-depth interviews with eight UIN Malang students from Pontianak, Sidoarjo, Indramayu, Bekasi, and Palangkaraya. Findings reveal that students from Malay-influenced regions (Pontianak and Palangkaraya) struggle more with fricative articulation than those from areas where the accent aligns more closely with Standard Indonesian (Sidoarjo, Indramayu, Bekasi). The most common errors include substituting /f/ with /p/ and /v/ with /b/, as well as replacing interdental fricatives with /s/, /t/, /d/, or /z/. These patterns result from phonological transfer, where L1 phonetic constraints shape L2 pronunciation, alongside the influence of exposure to diverse linguistic environments. These findings suggest that regional accents are not just linguistic variables but are also shaped by social and historical factors affecting foreign language acquisition. They underscore the need for pronunciation instruction that addresses accent-specific challenges rather than applying uniform teaching strategies. Language education policies should recognize regional phonetic diversity as a natural aspect of second language learning and develop more targeted pedagogical approaches to enhance pronunciation accuracy.